Digital-Driven Sustainable Innovation in Local Apparel Firms: A Case Study of PT. Tactical Outdoor - Ritus Ramadhana; Sony Sandra; Agus Mulyadi (International Journal of Business, Economics & Financial Studies, 2025)
The rapid digital transformation of the fashion industry and increasing environmental concerns have encouraged apparel companies to adopt sustainable innovation strategies to remain competitive. However, most studies on digital innovation and sustainability in the fashion sector focus on large multinational corporations, while empirical evidence from local creative industry firms in developing countries remains limited. This study aims to analyze sustainable innovation management practices in a digitally driven local apparel company, PT Tactical Outdoor, in Bandung, Indonesia. Specifically, the research explores how the company integrates market-based innovation, digital technology utilization, and leadership practices to support sustainable business development. The study employs a qualitative case study approach, with data collected through purposive in-depth interviews with the company owner and key staff members involved in innovation decision-making, technology management, and product development, conducted on January 6, 2025. Additional supporting data were obtained from company documentation, social media platforms, and relevant academic literature. The data were analyzed using thematic coding in NVIVO, complemented by SWOT and TOWS strategic analyses. The findings reveal that PT Tactical Outdoor manages innovation through three interconnected elements: market-based innovation, technology, and innovative leadership. Market intelligence derived from social media analytics, e-commerce data, and community engagement enables the company to identify emerging consumer needs and develop relevant products. Digital technologies such as ERP systems, digital design tools, and e-commerce platforms accelerate product development and support data-driven decision-making. Leadership plays a crucial role in fostering a culture of experimentation, collaboration, and sustainability within the organization. The study concludes that even small or local apparel firms can successfully implement sustainable innovation management when supported by digital technology, collaborative ecosystems, and adaptive leadership. These findings contribute to the literature by providing empirical insights into how digitally oriented local fashion brands can integrate innovation, sustainability, and digital transformation to achieve long-term competitiveness.